Food supply chains: coordination governance and other shaping forces - Anna Carbone (Agricultural and Food Economics, 2017)
The aim of this paper is twofold. First, it discusses how the functioning and performance of food chains are affected by the way stakeholders are embedded in the chains, by the coordination modes, and by the kind of governance. Second, by depicting six relevant agro-food chains, attention is raised on the kind of the stakeholders that participate in the chain and on the role of each with a special focus on possible drawbacks of an effective functioning of the supply chains. The chains outlined are (i) supply chains driven by a large retailer; (ii) supply chains driven by a global processing company; (iii) supply chains driven by a cooperative; (iv) supply chains for geographical indications; (v) short supply chains; and (vi) supply chains driven by a specialized high quality retailer. Special consideration is given to the positioning of farmers in each of the six chains and to the outcomes they get. It is shown how: (i) going spot on the marketplace may leave them with difficult market access and no bargaining power; (ii) being embedded in supply chains framed in the context of a captive governance may result in a squeeze of their profits as well as in unreliable market access; and (iii) supply chains are populated by reciprocal and pooled relationships and ruled by a more relational kind of governance, beside potentially bringing advantages in terms of decision power and economic benefits, also raises difficulties and drawbacks due to complexity of functioning, heterogeneity of stakeholders, and ambiguity of the nature of relations among them.
Keywords: 330; Hybrid institutions; Collective actions; Food; Coordination; Governance